A review of cereal grain proteomics and its potential for sorghum improvement. (November 2018) - Labuschagne, M.T.
Abstract: Cereals are an important source of calories and protein in the human diet. Endosperm makes up a large part of cereal grains and plays an important role in determining economic and nutritional value of cereals. Identification and characterization of endosperm proteins and determining factors influencing their synthesis and localization can facilitate enhancement of amino acid content and starch accessibility for improved grain nutritional value. In recent years, quantitative proteomics studies using mass spectrometry techniques have been contributing to information on plant growth, development and interactions with the environment. The combination of natural drought tolerance traits in sorghum and its complete genome sequencing in 2009 makes it a model plant for proteomics and genomics research. This paper reviewed recent developments in grain proteomics research of sorghum and other cereals such as maize, rice and barley. Significant progress is evident in proteomics of drought tolerance, grain development, grain proteins and amino acid composition of sorghum. The ideal would be to use this information to develop sorghum genotypes with characteristics such as high protein digestibility and improved amino acid composition, leading to increased nutritional value, especially for poor consumers in Africa. Highlights: Sorghum is an important food security crop. Proteomics of cereals has advanced significantly. A number of proteomic studies have been done on kafirins. High lysine sorghum mutants were analysed using proteomics. There is large scope for application of proteomics techniques in sorghum grains.